Broad spectrum antibacterial activity of granaticinic acid, isolated from Streptomyces thermoviolaceus NT1; an endophyte in Catharanthus roseus (L.) G. Don - Sudipta Roy,Debdulal Banerjee (Journal of Applied Pharmaceutical Science, 2015)
Searching for endophytic actinomycetes, strain NT1 was isolated from surface sterilized stem of Catharanthus roseus (L.) G. Don collected from Paschim Medinipur, India. The strain was identified as Streptomyces thermoviolaceus NT1 on the basis of morphological, biochemical and 16s rDNA based phylogenetic analysis. It showed potential antagonism against several Gram positive and Gram negative bacterial pathogens along with drug resistant Staphylococcus aureus. Maximum antibacterial production was obtained in ISP2 media at pH 7.2, 35 °C for 10 days. The active antibacterial substance was purified by Silica gel column chromatography and activity guided TLC. IR and NMR analysis identified the active compound as granaticinic acid of m/z 463.26 [M+H]. These results suggest that the antimicrobial produced by the isolated endophytic strain will be useful in near future.
Keywords: Endophyte,Streptomyces thermoviolaceus,granaticinic acid,antibacterial,drug resistance.